Preferences, Selection, and the Structure of Teacher Pay - Andrew C. Johnston (Institute of Labor Economics (IZA), 2021)
I conduct a discrete-choice experiment with responses linked to administrative teacher and student records to examine teacher preferences for compensation structure and working conditions. I calculate willingness-to-pay for a rich set of work attributes. High-performing teachers have similar preferences to other teachers, but they have stronger preferences for performance pay. Taking the preference estimates at face value I explore how schools should structure compensation to meet various objectives. Under each objective, schools appear to underpay in salary and performance pay while overpaying in retirement. Restructuring compensation can increase both teacher welfare and student achievement.
Keywords: I20; J32; J45; M50; 330; teacher labor markets; compensation structure; teacher quality